2020
DOI: 10.3390/ijms21072397
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Delirium in Older Persons: What We Should Not Do!

Abstract: The presentation of common acute diseases in older age is often referred to as “atypical”. Frequently, the symptoms are neither single nor tissue related. In most cases, the onset of symptoms and diseases is the expression of a diminished reserve with a failure of the body system and imbalance of brain function. Delirium is one of the main devastating and prevalent atypical symptoms and could be considered as a geriatric syndrome. It encompasses an array of neuropsychiatric symptoms and represents a disarrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 57 publications
0
22
0
2
Order By: Relevance
“…This situation may pose further diagnostic dilemmas, since the clinical manifestations of delirium superimposed on dementia are sometimes difficult to distinguish from the usual symptoms of dementia, especially in clinical contexts, where the personnel lacks geriatric training [26,27]. Moreover, the treatment of delirium superimposed on dementia in COVID-19 patients should be evaluated carefully, since many sedative drugs may contribute to worsen the respiratory failure and interact with QT-prolonging drugs, such as hydroxychloroquine and azithromycin, that are often prescribed for the treatment of SARS-COV-2 infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…This situation may pose further diagnostic dilemmas, since the clinical manifestations of delirium superimposed on dementia are sometimes difficult to distinguish from the usual symptoms of dementia, especially in clinical contexts, where the personnel lacks geriatric training [26,27]. Moreover, the treatment of delirium superimposed on dementia in COVID-19 patients should be evaluated carefully, since many sedative drugs may contribute to worsen the respiratory failure and interact with QT-prolonging drugs, such as hydroxychloroquine and azithromycin, that are often prescribed for the treatment of SARS-COV-2 infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…The progress of basic research and clinical research in recent years has shown that interventions for such patients are extremely important. Dynamic observation and accurate and effective treatment must be adopted to reduce the mortality rate (15,16). The S100B protein is an acidic calcium-binding protein, which is mainly found in astrocytes and oligodendrocytes of the central nervous system, and Schwann cells of the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…For older patients who need hospitalization, we suggest the creation of specific areas within the hospitals, to guarantee treatments tailored for frail patients. For instance, it is well known that non-pharmacological approaches are more effective than pharmacological ones in the prevention and treatment of hyperactive delirium [28].…”
Section: Older Patients Needing Hospitalizationmentioning
confidence: 99%